Úlceras por pressão: avaliação de riscos em pacientes internados em unidade de terapia intensiva: usando a escala de Braden - SENA, Suziane da Costa (2019)
The pressure ulcers or skin lesions are soft, superficial or deep that form due to lack of oxygen and/ or nutrients to meet the needs of the tissues. These are usually caused by pressure on an area of tissue, not allowing sufficient perfusion. It mainly affects patients in bed, and in intensive care units their occurrence is more frequent. This work it is an exploratory research with a quantitative approach that aimed to classify the risk of pressure ulcers of patients hospitalized through the Braden Scale, as well as assessing what the indicator of the scale was more affected in patients. The study sample consisted of 23 patients admitted to the Intensive Care Unit of the University Hospital João de Barros Barreto, from September to November 2011. To identify the risk scores used the Braden Scale and data contained in the records of patients. The Braden Scale has the indicator as follows: level of sensory perception, skin moisture, activity level, physical mobility, nutritional status, friction and shear. The activity index (bedridden), was most affected with 100%, and this indicator is influenced by the environment of the ICU that there does not have options for use of the patient as toilet seats, among others. The indicator friction and shear (problem) was also affected due to the clinical situation in which they were patients. The results presented indicate the need for implementation of the Braden Scale in the ICU of the institution researched, designed to make patient care more effective.